MACROPROLACTINEMIA IN A PATIENT WITH MICROPROLACTINOMA: A CASE REPORT - Niyaz, Mariyam; Vethakkan, Shireene; Ratnasingam, Jeyakantha; Lim, Lee-Ling; Ibrahim, Luqman; Paramasivam, Sharmila (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Macroprolactin is a prolactin-IgG complex that maybe be found in up to 15% of hyperprolactinemic sera, resulting in falsely elevated prolactin levels. Although macroprolactin usually has insignificant bioactivity, some patients report symptoms of hyperprolactinemia. Those with microprolactinomas could also have concurrent macroprolactin hence resulting in diagnostic dilemmas. RESULTS We report a 27-year-old nulliparous woman who presented with secondary amenorrhea for 8 months following a period of irregular menses for 2 years. She did not have headache or galactorrhea. She was within normal BMI and did not have features of Cushing’s, PCOS or hypopituitarism. Visual field assessment was normal. Investigations revealed high prolactin-3797 mIU/L(59-619 mIU/L) with LH-10.8 IU/L (1.0-15.0 IU/L), FSH-6.5 IU/L (2.0-10.0 IU/L), oestradiol-0.08 nmol/L(0.08 -0.53 nmol/L). Other pituitary hormones were normal and other causes of hyperprolactinemia were ruled out. Pitutiary MRI revealed a microadenoma, 2.6 mm X 4.2 mm. A diagnosis of microprolactinoma was made and cabergoline 0.25 mg biweekly was commenced. She regained her menses and prolactin dropped to 334 mIU/L at 4 months post-cabergoline. Despite good compliance, prolactin increased again, reaching a peak of 2011 mIU/L. Cabergoline dose was increased gradually to 0.5mcg thrice weekly, however prolactin remained >1000 mIU/L despite a significant period of treatment. Her menses remained normal throughout. Repeated MRI pituitary showed no change in size of microadenoma. She was then tested for macroprolactin with Polyethylene glycol (PEG) precipitation, which showed a PEG recovery of 37% in keeping with macroprolactinemia. Cabergoline was tapered off and she currently remains asymptomatic with normal menses. CONCLUSION The initial response to cabergoline suggests that this patient had concurrent microprolactinoma with macroprolactinemia. As macroprolactin may cause symptoms or occur with an underlying prolactinoma, there has been suggestion that all patients with hyperprolactinemia be screened for presence of macroprolactin. This could avoid unnecessary or prolonged treatment with dopamine agonists and reduce unnecessary investigations.